Development Of Pitch, Tempos, And Dynamics Learning Materials In Music Learning Based On Dalcroze Eurhythmics - Heldisari, Hana Permata; Ramadhan, Mohammad Ilham (Jurnal Seni Musik, 2021)
This study aims to produce a product in the form of learning materials for pitch, tempo, and dynamics with eurhythmic-based mp3 format. The theory used is music learning and eurhythmic dalcroze. This research is a research and development with ADDIE (Analysis-Design-Develop-Implement-Evaluate) learning design model. The trial subjects were 40 students who were taking Diatonic Music Theory courses in the 2020/2021 school year. Collecting data in this study using a questionnaire used to measure the feasibility of the product by material experts and product users. The data analysis technique used is descriptive statistics to determine the extent to which the product is feasible for use in the wider community. The result of this research is to produce a product in the form of teaching material about pitch, tempo and dynamics based on eurhythmic which is measurable its feasibility. Based on field trials, the product achieved an eligibility percentage of 93.3% with the category very feasible to use from the user's point of view, namely students as prospective teachers of cultural arts.